2001
DOI: 10.1146/annurev.immunol.19.1.225
|View full text |Cite
|
Sign up to set email alerts
|

Complexities of CD28/B7: CTLA-4 Costimulatory Pathways in Autoimmunity and Transplantation

Abstract: Recent advances in the understanding of T cell activation have led to new therapeutic approaches in the treatment of immunological disorders. One attractive target of intervention has been the blockade of T cell costimulatory pathways, which result in more selective effects on only those T cells that have encountered specific antigen. In fact, in some instances, costimulatory pathway antagonists can induce antigen-specific tolerance that prevents the progression of autoimmune diseases and organ graft rejection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
749
1
13

Year Published

2002
2002
2009
2009

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 960 publications
(782 citation statements)
references
References 165 publications
19
749
1
13
Order By: Relevance
“…The CTLA4 ligands have an inhibitory role on T cell activation and may contribute to peripheral tolerance (1). Upon B7-1 or B7-2 engagement, CTLA4 expressed on the surface of activated T lymphocytes signals for cell-cycle arrest and attenuating the function of effectors (2,3). Previous studies have demonstrated that blockage of signaling transduction between CD28 and CTLA4-Ig inhibited the response of T cells and prolonged the allograft survival in several rodent and organ transplantation models (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…The CTLA4 ligands have an inhibitory role on T cell activation and may contribute to peripheral tolerance (1). Upon B7-1 or B7-2 engagement, CTLA4 expressed on the surface of activated T lymphocytes signals for cell-cycle arrest and attenuating the function of effectors (2,3). Previous studies have demonstrated that blockage of signaling transduction between CD28 and CTLA4-Ig inhibited the response of T cells and prolonged the allograft survival in several rodent and organ transplantation models (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…CTLA-4 is a major costimulatory receptor that negatively regulates T cell activation [1][2][3][4]. CTLA-4 has a homologous structure to CD28 and binds to the same ligands, CD80/CD86, as CD28, but with much higher affinity.…”
Section: Introductionmentioning
confidence: 99%
“…These molecules may provide critical positive signals that augment and sustain T cell responses, or negative signals to attenuate or terminate immune responses [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%